UTILIZATION OF FOUR SUDANESE WILD FRUITS TO PRODUCE NECTARS - RAHMAN, NAWAL A. ABDEL-; ELRAKHA B. BABIKER, INNAM I. AWAD (Food Biology, 2018)
Doum (Hyphaene thebaica L), kirkir (Randia geipaeflora), karmadoda (Naucleae latifolia) and godeim (Grewia tenax) are some of the indigenous fruits in Sudan. The aim of this investigation is to process nectars from the edible part of these fruits. Doum and kirkir fruits were soaked in water in variable ratios for different durations of time to obtain the highest total soluble solids, total solids and total extractable matter. The pulps of karmadoda and godeim fruits were obtained mechanically by adding water, blanching and pulping with pulper machine. Results showed that soaking of doum and kirkir fruits at ratios 1: 4/2 h and 1: 4/8 h, respectively, were the most appropriate methods for extraction. The total solids (TS) obtained were 10.61 and 10.32 %, total soluble solids (TSS) 10.50 and 9.50%, and the total extractable matters (TEM) were 26.06 and 23.69%, respectively. However, blanching karmadoda fruit in water at a ratio of 1: 2/10 min gave total solids of 5.63% and total soluble solids of 5.00%. The nectars made were subjected to organoleptic evaluation. The results suggested that processing of nectars from forest fruits by direct extraction gave excellent sensory characteristics for human consumption.